Spatiotemporal Analysis of Land Use-Land Cover Changes in Pleistocene Uplifted Madhupur Tract Region using Geospatial Techniques (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The Madhupur Tract region of Bangladesh, characterized by Pleistocene uplifted terrain, is undergoing rapid and unplanned urbanization, marked by increased population density, industrial expansion, and infrastructure development. To highlight the environmental effects of urbanization on this previously unexplored region, this study uses geospatial approaches to assess the spatiotemporal changes in land use and land cover (LULC) in the Madhupur Tract. Utilizing multispectral Landsat images from 2000, 2010 and 2023, LULC maps were generated using unsupervised classification methods in ArcGIS. Indices such as the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Normalized Difference Built-up Index (NDBI) were employed to evaluate land cover dynamics and spatial patterns for the years 2000, 2005, 2010, 2015 and 2023. Results revealed significant land cover changes over the study period, with a marked decline in forest cover and agricultural land and a substantial increase in settlement areas due to urban growth. From 2000 to 2023, forest cover decreased from 29% to 11%, while settlements expanded from 10% to 30%, indicating extensive urbanization and deforestation. NDVI analysis showed fluctuations in vegetation health, with sparse vegetation decreasing and barren land increasing significantly, reflecting ongoing land degradation. NDWI results indicated a dramatic reduction in water bodies, declining from 30% coverage in 2000 to just 6% in 2023. The findings of this study provide critical insights into the complex interplay between urban expansion and environmental degradation within the Madhupur Tract, emphasizing the region’s vulnerability to unsustainable development practices. By documenting the loss of natural landscapes and the intensification of built-up areas, this research highlights the urgent need for integrating sustainable land management and urban planning policies to balance economic development with environmental conservation.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 19-32